Intense vacuum ultraviolet and infrared scintillation of liquid Ar-Xe mixtures. (15th January 2015) - Neumeier, A.; Dandl, T.; Heindl, T.; Himpsl, A.; Oberauer, L.; Potzel, W.; Roth, S.; Schönert, S.; Wieser, J.; Ulrich, A.
Abstract: Vacuum ultraviolet light emission from xenon-doped liquid argon is described in the context of liquid noble gas particle detectors. Xenon concentrations in liquid argon from 0.1 ppm to 1000 ppm were studied. The energy transfer from the second excimer continuum of argon to the second excimer continuum of xenon is observed by recording optical emission spectra. The transfer almost saturates at a xenon concentration of for which, in addition, an intense emission in the infrared at a peak wavelength of with photons per MeV deposited by electrons had been found. The corresponding value for the VUV emission at a peak wavelength of 174 nm (second excimer continuum of xenon) is determined to be photons per MeV electron energy deposited. Under these excitation conditions pure liquid argon emits photons per MeV electron energy deposited at a peak wavelength of 127 nm. An electron-beam–induced emission spectrum for the 10 ppm Ar-Xe liquid mixture ranging from 115 nm to is presented. VUV emission spectra from xenon-doped liquid argon with exponentially varied xenon concentrations from 0.1 ppm to 1000 ppm are also shown. Time structure measurements of the light emissions at well-defined wavelength positions in the vacuum ultraviolet as well as in the near-infrared are presented.